2014
DOI: 10.17219/acem/37245
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Interstitial Cells of Cajal of the Upper Urinary Tract

Abstract: Interstitial cells of Cajal (ICCs) were discovered in the gastrointestinal tract over 100 years ago and since then numerous digestive tract pathologies involving ICCs have been described. Many researchers explored ICCs presence and function in the upper urinary tract. Currently, we know that ICCs have potential plasticity, their own spontaneous activity and that they are responsible for Ca 2+ waves generation and neuromuscular transmission. ICCs are also involved in the conjugation, propagation and modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…Recent studies indicated that interstitial cells of Cajal like cells (ICC-LC) expressing the c-kit gene, which are sparsely distributed within the lamina propria and muscle layer of upper urinary tract, play an important role in promoting pyeloureteric peristalsis [39]. ICC-LC are electrically active and responsible for conduction of slow-wave potentials for peristaltic movements [40]. Contraction waves generated in the renal pelvis are probably propagated, coordinated and modulated in the upper urinary tract by ICC-LC [41,42].…”
Section: Plcl -Poly (L-lactide-co-caprolactone); Pga/plga -Polyglicolmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated that interstitial cells of Cajal like cells (ICC-LC) expressing the c-kit gene, which are sparsely distributed within the lamina propria and muscle layer of upper urinary tract, play an important role in promoting pyeloureteric peristalsis [39]. ICC-LC are electrically active and responsible for conduction of slow-wave potentials for peristaltic movements [40]. Contraction waves generated in the renal pelvis are probably propagated, coordinated and modulated in the upper urinary tract by ICC-LC [41,42].…”
Section: Plcl -Poly (L-lactide-co-caprolactone); Pga/plga -Polyglicolmentioning
confidence: 99%
“…Contraction waves generated in the renal pelvis are probably propagated, coordinated and modulated in the upper urinary tract by ICC-LC [41,42]. ICCs, thanks to their automatism, are able to replace discontinued atypical SMCs impulses and maintain peristaltis of lower ureter parts [40,43]. In vitro isolation and culture of ICC-LC from the urinary tract has not yet been established, but taking into consideration previous works and our experience on urinary conduit construction, addition of these cells or coculture of them with smooth muscle cells can potentially accelerate the restoration of peristaltic waves on the reconstructed segment, which could prevent development of hydronephrosis.…”
Section: Plcl -Poly (L-lactide-co-caprolactone); Pga/plga -Polyglicolmentioning
confidence: 99%
“…The "funny" (If) current (or funny channel or pacemaker current), originally described in the sinoatrial (SA) node and Purkinje fibers, is currently being investigated for its potential role(s) in smooth muscles with the capacity of generating spontaneous phasic activity. [7][8][9][10]11 Evidence is being accumulated that interstitial cells of Cajal (ICCs) and ICC-like cells possess the general and specific properties of pacemaker cells. Although less studied than those in cardiac tissue, they are ubiquitously expressed in smooth muscle tissues of many organs, including the gastrointestinal tract, uterine, lymph ducts, urinary bladder, and urethra.…”
Section: Introductionmentioning
confidence: 99%
“…Although less studied than those in cardiac tissue, they are ubiquitously expressed in smooth muscle tissues of many organs, including the gastrointestinal tract, uterine, lymph ducts, urinary bladder, and urethra. 8,9 The pacemaker structures have been suggested to contribute to spontaneous contractions of these smooth muscle tissues by funny currents (If currents) through hyperpolarization-activated cyclic nucleotide-gated (HCN) channels. 9,12 Indeed, the self-contractibility of the urinary bladder through myogenic excitation implicates a potential bladder pacemaker, possible through the signals from ICCs.…”
Section: Introductionmentioning
confidence: 99%
“…Outros autores evidenciaram, de modo semelhante, diversas alterações histológicas na estenose da JUP, como deposição aumentada de elastina, aumento da deposição de colágeno peri e intrafascicular, redução da quantidade e orientação errática das fibras musculares, assim como redução dos elementos neurais e das células intersticiais de Cajal, um tipo de célula que, como um marca-passo, desencadeia a contração dos tecidos (11,12) . As células intersticias de Cajal foram descobertas no trato gastrointestinal há mais de 100 anos, e mais recentemente sua ação no trato urinário superior vem sendo também estudada (13) .…”
Section: Introductionunclassified